NiO-CGO Composite for SOFC Anode: Synthesis and Characterization - Cela, Beatriz (2010)
In this work compounds of gadolinium-doped ceria, Ce0.9Gd0.1O1.95 (CGO) and NiO were synthesized by polymeric precursor method. NiO-Ce0.9Gd0.1O1.95 composite was attained by mixture of the powders of the both phases calcinated already. The precursor powders were characterized by simultaneous thermogravimetry-differential thermal analysis and the calcined materials were studied by X-ray diffraction, scanning electronic microscopy, Fourier transform infrared spectroscopy and dilatometry. The refinement of the diffraction data indicated that the powders were crystallized in the wanted phases. All the produced powders had nanometric and sub micrometric features. The produced composite showed good characteristics for the use as anode for SOFC.